2022
DOI: 10.1038/s41598-022-08977-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wind and light on the floating and sinking process of Microcystis

Abstract: The vertical migration and accumulation of Microcystis colonies is a critical process in algal bloom formation. This work explored the effect of wind and light intensity on the vertical migration of Microcystis colonies. The wind-driven currents, light-driven changes in mass density of colonies, and the effect of colony size was coupled to simulate the vertical motion of colonies via Ansys Fluent and MATLAB. Results showed that light causes Microcystis to exhibit a ‘day-sinking and night-floating’ (d-n) phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This is consistent with a recent field study where the peak total horizontal biomass transport rate was observed at a wind speed of 2.1 m/s . The observed trends can be attributed to the sinking of algal colonies under wind-induced turbulent forces. , These colonies reach a balance between buoyancy and turbulence and drift with water currents. To demonstrate this, we used a one-dimensional (1D) hydrodynamic model and a recent in situ observational study to simulate vertical wind-induced current profiles (Text S3 of the Supporting Information).…”
Section: Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with a recent field study where the peak total horizontal biomass transport rate was observed at a wind speed of 2.1 m/s . The observed trends can be attributed to the sinking of algal colonies under wind-induced turbulent forces. , These colonies reach a balance between buoyancy and turbulence and drift with water currents. To demonstrate this, we used a one-dimensional (1D) hydrodynamic model and a recent in situ observational study to simulate vertical wind-induced current profiles (Text S3 of the Supporting Information).…”
Section: Results and Discussionsupporting
confidence: 90%
“…Moreover, greater wind-induced turbulence causes colonies to sink deeper. For example, a recent simulation study demonstrated that, at 2 m/s wind speed, colonies with a size of 500 μm diameter floated at around 7 cm depth, but at 3 m/s, they sank to about 33 cm depth . In our simulations, at 2 m/s wind speed, the current velocity at 7 cm depth was 7.47 cm/s.…”
Section: Results and Discussionmentioning
confidence: 41%
“…Based on the TKEz de nition, it was not only the variance of velocity, but also could describe the turbulence intensity, with both statistical and hydraulic signi cance. From the perspective of application prospects, many large shallow lakes are affected by water blooms (Rousso et al, 2020), and the TKEz could be used as a key factor in predicting water blooms (Xue et al, 2022). The TKEz could therefore play an essential role in lake management and is worthy of being one of the key factors for lake monitoring.…”
Section: Characterization Of Ow Eld Driven By Windmentioning
confidence: 99%
“…Cyanobacteria biomass is closely related to nutrient concentration (Xu et al, 2014), but most blooms are formed by the oating and horizontal accumulation of algae. The ability to oat is closely related to the size of colonies and turbulent kinetic energy (TKE) (Xue et al, 2022). The horizontal accumulation of Microcystis after oating and TKE in lakes is closely related to wind-driven currents (George et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Although the algae biomass size is not determined by external factors in essence, wind fields can increase the availability of light, heat, and nutrients by affecting water mixing, heat stratification, transfer and exchange, and the upwelling of nutrients [21,28,29]. The wind and wind-induced currents play critical roles in the floating-sinking process of algae and the variability of algae biomass will increase with increasing variability in wind speed [19,30]. Continuous or strong winds can not only directly disperse algal blooms, but also alter the distribution of nutrients over a longer time scale by eroding density gradients and deepening mixing, leading to changes in biomass concentration [31].…”
Section: Introductionmentioning
confidence: 99%